Tanzania Engaging the Private Sector in Education : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2015)
As countries redouble their efforts to achieve learning for all at the primary and secondary levels, the private sector is a resource for adding capacity to the education system. This report presents an analysis of how effectively the current policies in Tanzania engage the private sector in basic (primary and secondary) education. The analysis draws on the engaging the private sector (EPS) framework, a product of the World Bank’s systems approach for better education results (SABER). SABER EPS research in Tanzania has found that access to primary education is nearly universal; however enrolments at the secondary level are low. The report provides an overview of SABER EPS, followed by a description of the basic education system in Tanzania, with a focus on the private sector and government policies related to private provision of education. The report benchmarks Tanzania’s policy environment utilizing the SABER EPS framework, and finally offers policy options to enhance learning for all children in primary and secondary school.